The impenetrability of criminal action as an effective criminal policy against corruption - Gerónimo De La Cruz, Jaime (2023)
Corrupt acts committed within state institutions by a minority of individuals for personal gain are socially and legally unacceptable, as they distort the collective objectives of public administration and affect society in general, as corruption prevents altruistic activities (hospitals, schools, bridges, roads) from being carried out for the benefit of citizens. On the contrary, the rate of corruption in our country is on the increase, but the most scandalous thing is that these people, who are dedicated to diverting public goods or services, are free from the weight of justice, as they manage to flee the country until the criminal case against them expires and are exempt from any criminal sanction. In this line of thought, the study focuses on determining whether the imprescriptibility of criminal acts is an effective criminal policy to combat impunity in acts of corruption and, consequently, to reduce its criminal index to the extent that it is constituted as a means of general and special prevention, since it will be useless for them to try to flee from the Peruvian administration of justice, since the criminal action against them will not be subject to the statute of limitations.